Integrated Evaluation of Disability - Vinayagam, Ramar Sabapathi (Milton : Chapman and Hall/CRC, 2018)
There are overwhelming demands for health and rehabilitation services due to rise in the number of disabled people. The existing literature on disability evaluation has only focused on impairment or functional limitation or earning capacity. They have not considered the skills fundamental to live, learn and work successfully in the community. This book addresses integrated evaluation of disability using 'Clinical Tools', 'Activity Participation Skills Assessment Scale', 'Personal Factors Measurement Scale', and 'Environmental Factors Measurement Scale'. Physicians from all disciplines can use this method to evaluate disability pertaining to their respective fields. Key Features Applies the principles of 'World Health Organization's International Classification of Functioning, Disability and Health - ICF' Includes case studies in the hypothetical model in this book Includes a Ready Reckoner Impairment Table provides impairment score for 120 common clinical conditions Consists of an integrated software which computes percentage of disability for clinical conditions
2.2.7.3 Biopsychosocial approach2.2.8 World Bank (2007); 2.2.9 Americans with Disabilities Act of 1990 (2009); 2.2.10 World Disability Report (2011); 2.2.11 Prevailing methods of disability evaluation in other countries; 2.2.12 Prevailing methods of disability evaluation based on ICF; 2.3 Integrated Evaluation of Disability; 2.3.1 Concept of the Integrated Evaluation of Disability; 2.3.2 Need for an integrated evaluation; 2.3.3 Scope of an Integrated Evaluation of Disability; 2.3.4 Integrated Evaluation of Disability-Illustrations; 2.3.4.1 Flaccid paralysis-Right lower extremity
Description based upon print version of record.
2.3.4.2 End-stage renal disease
OCLC-licensed vendor bibliographic record.
Keywords: Disability evaluation; MEDICAL / Family & General Practice; MEDICAL / Occupational & Industrial Medicine; MEDICAL / Psychiatry / General